2021
DOI: 10.1007/s41030-021-00153-w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Practice Patterns of COPD: A Survey of Physicians in Nepal, Sri Lanka and Malaysia

Abstract: Introduction: There is much recent data from Nepal, Sri Lanka and Malaysia that can help us understand the practice patterns of physicians regarding the diagnosis and management of chronic obstructive pulmonary disease (COPD) in these countries. We conducted this survey to understand the practice patterns of physicians related to the diagnosis and management of COPD in these three countries. Methods: This questionnaire-based, observational, multicentre, cross-sectional survey was carried out with 438 randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We found that seventy three percent of the respondents think inhaler therapy as the first line therapy for managing COPD while Chokhani et al reported 54 percent of the physicians prescribe inhaler therapy to all COPD patients. 4 It was found that only twenty three percent of the respondents used to check the technique of the use of inhaler devices during follow up which was similar to Chokhani's another study in which 39.95% of the physicians evaluated their patients' inhalation technique on every visit. 4 Forty one percent of the respondents said that they told the method of inhalation technique while prescribing the inhalation therapy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We found that seventy three percent of the respondents think inhaler therapy as the first line therapy for managing COPD while Chokhani et al reported 54 percent of the physicians prescribe inhaler therapy to all COPD patients. 4 It was found that only twenty three percent of the respondents used to check the technique of the use of inhaler devices during follow up which was similar to Chokhani's another study in which 39.95% of the physicians evaluated their patients' inhalation technique on every visit. 4 Forty one percent of the respondents said that they told the method of inhalation technique while prescribing the inhalation therapy.…”
Section: Discussionsupporting
confidence: 56%
“…[1][2][3] The practice of inhaler therapy varies among different treating physicians in different part of the world. 4 The patients can be appropriately instructed only if the health care providers themselves are well trained to do so. 5 Different studies have shown that there is inadequate knowledge of the inhaler therapy among the patients, and also the health care workers including nurses who themselves teach the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In equation (1) , E i, j is the observed change from baseline in pre-dose (trough) FEV 1 (L) at the time point j in the i th arm, and E max,i represents the maximal change from baseline in trough FEV 1 (L) in the i th arm. τ i is the loss of efficacy rate in the i th arm, while ε i, j is the residual error at the time point j in the i th arm, which is weighted by the inverse of the square root of the sample size ( N i, j ), assumed to be normally distributed, with a mean of 0 and variance of σ 2 . The residual errors are smaller in the arm with larger sample sizes.…”
Section: Methodsmentioning
confidence: 99%
“…η 1, i and η 2, i represent the interstudy variability of E max and τ , respectively. E max and τ are assumed to be normally distributed, with means of 0 and variances of ω 1 2 and ω 2 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation